Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas VIII MTs Hayatul Islamiyah Pangean - Andika, Shavani; Solfitri, Titi; Kartini (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research is motivated by the low mathematics learning outcomes of eighth-grade students at MTs Hayatul Islamiyah Pangean, which are caused by a teaching process that revolves around the teacher. One way to address this is by implementing the Problem-Based Learning model. This type of research is classroom action research that consists of two cycles. Each cycle includes planning, implementation, observation, and reflection. This action was carried out at MTs Hayatul Islamiyah Pangean in the second semester of the 2022/2023 academic year with 20 eighth-grade students. The research instruments used were instructional materials consisting of the syllabus, lesson plans, and student worksheets, while the data collection instruments consisted of observation sheets and student learning outcome tests. Data were analyzed based on the students' observations and mathematics learning outcome tests. The research results show that implementing the Problem-Based Learning model can improve students' mathematics learning outcomes. The average score of mathematics learning outcome tests increased from 55 in cycle I to 90 in cycle II. Thus, applying the Problem-Based Learning model can improve the learning process and enhance the mathematics learning outcomes of eighth-grade students at MTs Hayatul Islamiyah Pangean.